2020
DOI: 10.9778/cmajo.20200095
|View full text |Cite
|
Sign up to set email alerts
|

Incidental detection, imaging modalities and temporal trends of differentiated thyroid cancer in Ontario: a population-based retrospective cohort study

Abstract: T here is debate and concern about a worldwide epidemic of thyroid cancer overdiagnosis. 1,2 Several factors suggest that a large reservoir of indolent thyroid cancers is being detected by sensitive imaging techniques. Incidence rates of thyroid cancer are increasing worldwide in every continent except Africa, whereas mortality rates from thyroid cancer are low and relatively stable. [3][4][5] Large increases in the registrations of differentiated thyroid cancers (≥ 90% of thyroid cancer cases 6 ) and subclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…In our study, the proportion of incidentally detected thyroid cancer increased from 36% in 2011 to 82.3% in 2018. This phenomenon has also been reported in several other countries, such as Japan, Canada, and the USA ( 8 , 9 , 17 ), which suggests that increased imaging and diagnostic scrutiny may have contributed significantly to the upsurge of thyroid cancer incidence observed ( 18 ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In our study, the proportion of incidentally detected thyroid cancer increased from 36% in 2011 to 82.3% in 2018. This phenomenon has also been reported in several other countries, such as Japan, Canada, and the USA ( 8 , 9 , 17 ), which suggests that increased imaging and diagnostic scrutiny may have contributed significantly to the upsurge of thyroid cancer incidence observed ( 18 ).…”
Section: Discussionsupporting
confidence: 61%
“…Overall, our finding on the proportion of non-incidentally detected PTC is consistent with a multicenter study involving four countries (the USA, Canada, Denmark, and South Africa), which showed that 30% of the thyroid cancer cases were identified through symptoms ( 15 ). But the large variation across centers – for example, incidentally detected cases accounted for only 18% male and 11% female cases during 2013–2017 in Ontario, Canada ( 8 ) but as high as 62% of all cases during 2013–2016 in Queensland, Australia ( 16 ) – highlights the impact of local health-care system and medical practice. With the widespread use of diagnostic imaging and fine-needle aspiration biopsy over the past years, a growing number of thyroid cancers had been discovered incidentally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation